Digital Transformation Empowers Green Innovation in Manufacturing: Strategic Synergy and Implementation Pathways of Geely Group - Xiao, Wei; Liu, Hongmin; Liu, Yingchen; Yu, Haiming (Global Sustainability Research, 2026)
Confronted by the dual imperatives of global carbon neutrality commitments and digital transformation trends, compounded by China’s “dual carbon” strategy and digital technological revolution, manufacturing enterprises face a critical challenge to synergize low-carbon development with digitalization. Drawing on strategic synergy and dynamic capabilities theories, this study adopts a single-case approach, focusing on Geely Group, to systematically analyze its dual-driven strategic architecture and implementation pathways integrating digitalization and green low-carbon transitions. Findings reveal that Geely has constructed a bidirectionally enabling and closed-loop iterative transformation model through a four-dimensional mechanism: strategic guidance, organizational enabling, technological fusion, and ecosystem collaboration. Specifically, digital technologies serve as precise instruments for carbon reduction in production, energy management, and green product innovation, while green low-carbon objectives, in turn, drive deeper integration of digital technologies in R&D and applications. Theoretically, this study uncovers a synergistic coupling effect achieved through strategic design of digital and green transformations, overcoming the theoretical limitations of isolated transition paradigms and offering an integrated analytical framework for understanding “dual-transformation synergy.” Practically, it provides actionable synergistic strategies and implementation pathways for manufacturing enterprises navigating carbon neutrality and digitalization pressures, contributing a contextually relevant Chinese solution with theoretical and practical implications.